Benefits of using STEAM technologies in science lessons in primary education - Yusupova Sugdiyona Umidovna (Euro Asian Journal Publishing, 2024)
This article examines a modern approach to teaching in elementary school, which integrates science, technology, engineering, art and mathematics (STEAM), and how the integration of STEAM technologies into the educational process effectively promotes the development of student skills, including critical thinking, creativity and teamwork. Emphasis is placed on the benefits of using virtual laboratories, interactive applications, and multimedia resources in science lessons.
Keywords: primary school age; integration; modern world